The Contribution of Financial Literation and Human Capital In Improving The Performance of Village-Owned Business Agencies - M. Ihsan; Burhanuddin Ladjin; Fatma Fatma; Arif Widyatama; Tri Rahmat (Media Komunikasi FPIPS, 2021)
The purpose of this study is to examine the relationship between financial literacy and human capital on the performance of Village-Owned Enterprise. Village-Owned Enterprise has an important role in building the economy in the village. However, the condition that occurs is that there are still many conditions of rural community human resources, especially Village-Owned Enterprise officials, who do not have good management skills and financial literacy in managing Village-Owned Enterprise. This research uses explanatory research, research sites are in Sigi and Poso Regencies. The population of this research is the management of Village-Owned Enterprise in Sigi and Poso Regencies, amounting to around 300 people representing each village in Sigi and Poso Regencies. Based on the results of the questionnaire distribution, a sample of 75 Village-Owned Enterprise administrators in Sigi and Poso districts was obtained. Financial literacy in Sigi village and even more so in Poso district is still far from perfect, because Village-Owned Enterprise administrators in SIGI and Poso in general are unable to use village participation funds accountably. This is due to the weak capacity of Village-Owned Enterprise administrators in managing Village-Owned Enterprise planning, implementation and financial reporting. The results of this study prove that the human capital of Village-Owned Enterprise administrators has an effect on Village-Owned Enterprise performance. This indicates that the community, including Village-Owned Enterprise administrators, has the potential to innovate so that it will have an impact on Village-Owned Enterprise performance.